Metrics for land-scarce agriculture - DeFries, Ruth S.; Fanzo, J.C.; Remans, R.; Palm, Cheryl A.; Wood, S.; Anderman, T.L. (American Association for the Advancement of Science, 2015)
Nutrient content must be better integrated into planning